Educational renewal better teachers, better schools - Goodlad, John I. 1920- (Jossey-Bass, 1994)
What comes first - good schools or good teacher education programs? The answer, according to John I. Goodlad, is that both must come together. In his new book, Goodlad picks up where he left off in Teachers for Our Nation's Schools - providing the vision and rationale behind "centers of pedagogy" that can bring schools and universities together in a close, renewing relationship. In Educational Renewal, Goodlad proposes a redesign of education that is grounded in a mission of enculturating the young in a social and political democracy. He details his vision of centers of pedagogy and answers many of the questions raised by his earlier work. Why have centers of pedagogy? Who are the faculty? How protected are the borders of centers of pedagogy to be? And how do partner or professional development schools fit into the scheme? True educational renewal, Goodlad says, requires the continuous examination of institutional purpose, roles, and responsibilities in order to avoid the stagnation that has all too often characterized teacher education. New curriculum development, the establishment of school-university partnerships, the transformation of school and university cultures, and collaboration with outside agencies are just a few of the examples Goodlad includes to illustrate his extensive research on improving teacher education and schools.
Keywords: Enseignants - Formation - États-Unis; Sciences de l'éducation - Étude et enseignement (Supérieur) - États-Unis; Sciences de l'éducation - Étude et enseignement (Supérieur) - États-Unis - Programmes d'études; Erziehung; Lehrer; Education -- Study and teaching (Higher) -- Curricula -- United States; Education -- Study and teaching (Higher) -- United States; Teachers -- Training of -- United States; Qualitätssteigerung; Evaluation; Schulreform; Lehrerbildung; Höhere Schule; USA